Short Communication: The diversity of wild Dendrobium (Orchidaceae) in Central Bali, Indonesia - IDA AYU PUTRI DARMAWATI; I NYOMAN RAI; RINDANG DWIYANI; IDA AYU ASTARINI (Biodiversitas Journal of Biological Diversity, 2018)
Darmawati IAP, Rai IN, Dwiyani R, Astarini IA. 2018. The diversity of wild Dendrobium (Orchidaceae) in Central Bali, Indonesia. Biodiversitas 19: 1110-1116. Dendrobium is the largest orchid genus of the Orchidaceae family. The research aimed to explore the species diversity of Dendrobium, dominance, and species similarity in some forest of Bali. The explored locations were grouped to lowland about 0-700 m asl. (Tejakula, Bukit Silangjana, Sepang Kelod, Mekori, and Busungbiu), transition land about 700-1100 m asl. (Sepang Kaje and Jatiluwih) and lower montane 1100-1500 m asl. (Natural Reserves of Lake Buyan-Tamblingan, Puncak Landep, and Lemukih). There were 24 species of Dendrobium in Central Bali, 2 spesies of which were not identified. The dominant species were D. acuminatissimum, D. crumenatum and D. linearifolium. The highest species diversity index of wild Dendrobium was present in lowland (16 species, 66.66%) followed by those in transition land and lower montane (12 species, 50.00% and 6 species, 20.83%, respectively). The pattern is also similar either for the species prosperity (3.875; 3.094, and 0.699, respectively). Uniformity of wild Dendrobium on transition land was 0.922, followed by those in lowland and lower montane (0.864 and 0.794). There were 6 similar species of Dendrobium found in lowlands and lower montane (42.857% equality index) and 2 similar species in lowlands and lower montane (19.047% equality index) and also 2 similar species in transition land and lower montane (23.359% equality index). D. macrophylum, D. heterocarpum and D.secundum, their presence are pronely threatened with extinction so conservation is necessary.